2005
DOI: 10.1902/jop.2005.76.2.210
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Recombinant Human Bone Morphogenetic Protein‐2 on the Repair of Alveolar Ridge Defects in Baboons

Abstract: TCP/HA/ACS and alphaBSM appear to be suitable carrier technologies for rhBMP-2. Alveolar augmentation procedures using either technology combined with rhBMP-2, rather than stand-alone therapies, may provide clinically relevant augmentation of alveolar ridge defects for placement of endosseous dental implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 25 publications
1
44
0
1
Order By: Relevance
“…BMPs have been shown to increase the formation of bone nodules in vitro [45][46][47][48][49][50][51][52][53][54][55][56] and stimulate bone formation in vivo. But the dosage applied in these clinical studies was several orders of magnitude higher than the concentration of naturally occurring BMPs [57].…”
Section: Discussionmentioning
confidence: 99%
“…BMPs have been shown to increase the formation of bone nodules in vitro [45][46][47][48][49][50][51][52][53][54][55][56] and stimulate bone formation in vivo. But the dosage applied in these clinical studies was several orders of magnitude higher than the concentration of naturally occurring BMPs [57].…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] BCP has been also used as a carrier for rhBMP-2 in the alveolar ridge defect 21 and spine fusion 22,23 models. Jung et al 24 evaluated rhBMP-2-loaded HA/TCP in the rabbit calvarial onlay model, and concluded that this might be an ideal carrier system for rhBMP-2.…”
Section: Introductionmentioning
confidence: 99%
“…They have included dose-variation (Tatakis et al 2002), the use of space-providing macroporous membranes or titanium mesh devices to shield the rhBMP-2/ACS from compressive forces reducing the potential volume for tissue to form into Lee et al 2013b), as well as supplementing the ACS with bulking agents to withstand compressive forces compromising bone augmentation (Barboza et al 2000(Barboza et al , 2004Miranda et al 2005;Lu et al 2013). Whereas Sigurdsson et al (1997), figure copyrighted by and modified with permission from Wiley-Blackwell dose-variation (rhBMP-2 at 0.05, 0.1, and 0.2 mg/mL) significantly failed to influence rhBMP-2/ACS-induced bone formation (Tatakis et al 2002), the use of macroporous space-providing devices allowed significantly enhanced rhBMP-2/ACS (rhBMP-2 at 0.2 mg/mL)-induced bone formation/alveolar augmentation compared with unshielded sites supporting the tissue engineering principle that the geometry/volume of new bone formation can be ascertained in the design of a space-providing device/matrix (Fig.…”
Section: Alveolar Augmentationmentioning
confidence: 99%
“…However, bulking agents also introduce compromises related to biodegradation; slowly or nonresorbable biomaterials may compromise the structural integrity of the newly formed bone including osseointegration of dental implants (Barboza et al 2000(Barboza et al , 2004Miranda et al 2005;Lu et al 2013) while for bioresorbable conduits the resorption process per se may solicit inflammatory reactions compromising bone formation and/or maintenance (Sigurdsson et al 1996). Critical-size, supraalveolar, peri-implant defects treated with rhBMP-2/ACS (0.2 mg/ mL), a porous, space-providing ePTFE membrane for guided tissue regeneration, or rhBMP-2/ACS combined with the porous, ePTFE membrane.…”
Section: Alveolar Augmentationmentioning
confidence: 99%